Implementasi Sistem Keuangan Digital dalam Meningkatkan Akuntabilitas Pengelolaan Dana Pendidikan: Implementing a Digital Financial System to Improve Accountability in Education Fund Management - Dewi Anggreini; Tiara Apriani; Dinda Tiyas Ningsih (Al-Gafari : Manajemen dan Pendidikan, 2026)
The development of information technology has encouraged educational institutions to implement digital financial systems in managing educational funds. This study aims to analyze the implementation of digital financial systems in improving the accountability of educational fund management and to identify the supporting and inhibiting factors in their implementation. This research employed a descriptive qualitative approach using a literature study method. Data were collected through documentation techniques by reviewing various scientific journals, books, and supporting documents related to digital financial systems and accountability in educational financial management. The findings indicate that the implementation of digital financial systems contributes positively to increasing transparency, effectiveness, accuracy of financial recording, and ease in preparing financial accountability reports. In addition, digital financial systems support monitoring processes and minimize administrative errors in managing educational funds. However, several challenges remain, including limited human resource competencies, unstable internet connectivity, and inadequate supporting facilities. Therefore, improving technological competencies and providing adequate supporting infrastructure are necessary to ensure the optimal and sustainable implementation of digital financial systems in educational institutions.